Sestrin2 Overexpression Inhibits Proliferation and Epithelial–Mesenchymal Transition and Induces Autophagy Through the AMPK/mTOR Signaling Pathway in Human Prostate Cancer Cells - Yae-Ji Kim; Hui-Ju Lee; Kyung-Hyun Kim; Geum-Lan Hong; Ju-Young Jung (Prostate Cancer)
Conclusion: Our study suggests that SESN2 inhibits prostate cancer cells by inducing autophagy through the AMPK/mTOR signaling pathway. These results indicate that SESN2 might be a novel target for prostate cancer.